Demographic determinants of regional development in Eastern Poland - Łukasz Karol Bugowski (Economic and Environmental Studies (E&ES), 2019)
Research Background: Demography affects human capital, which today is one of the most important factors of regional development. Demographic factors create possibilities or limit the expansion of the knowledge and skills and condition socio-economic activity. In other words, demography can favour or block regional development. Negative demographic trends, in particular referring to the size and structure of the population as well as population growth, are a significant challenge of regional policy. In addition, in the case of regions with a lower level of development, the migration rate is negative, which in turn may limit regional development. As a consequence, the following hypothesis will be verified in the article: demographic processes are a barrier to the development of regions in Eastern Poland. Purpose of the paper: The main objective of the article is to analyze the spatial diversity of demographic phenomena in Eastern Poland, along with the identification of areas with unfavorable demographic developmental conditions. Implementation of the second objective is to carry out the analysis at the level of subregions, not regions, which will allow for more precise analysis of negative demographic phenomena. Methodology/Methods/Data sources: In the article the method of linear ordering of objects using the taxonomic measure of Z. Hellwig's development is used. In addition, a comparative analysis of the main demographic phenomena in 2010, 2013 and 2016 in Eastern Poland was carried out. The main source of data used in the article was the Statistics Poland (Local Data Bank). Findings: The analysis allows to conclude that in 2010-2016 in Eastern Poland an increase in the demographic burden resulting from the aging population was observed. In addition, the migration rate is negative and sub-replacement fertility rate is common in the majority of the subregions. As a consequence, negative demographic phenomena are increasingly limiting human capital and indirectly have a negative impact on regional development. However, the conducted analysis allows to distinguish subregions with positive values of the analyzed indicators, but it refers only to a few regions including a capital of a given voivodeships, and do not significantly affect the negative general demographic trends in Eastern Poland.
Keywords: J10; O15; R10; 330; regional development; demographic processes; demographic structure; natural population growth; migrations; Eastern Poland